VENTRICULAR ARRHYTHMIA POST I-131-METAIODOBENZYLGUANIDINE (MIBG) THERAPY IN AN INOPERABLE RIGHT RETROPERITONEAL PARAGANGLIOMA - Amirulhusni, Athirah Nur; Nordin, Hidayatil Alimi Keya; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Paraganglioma is a rare neuroendocrine tumour arising from extra-adrenal paraganglia. First-line treatment involves surgical resection; however, a proportion of patients present with unresectable tumours. I-131-metaiodobenzylguanidine (MIBG) therapy has emerged as a systemic treatment option for inoperable disease. Though rare, MIBG therapy can potentially cause ventricular arrhythmia due to catecholamine surge via tumour cell lysis. This case describes a patient presenting 3 weeks after therapy with ventricular tachycardia. CASE A 49-year-old male with underlying hypertension, diabetes mellitus, ischaemic heart disease post-angioplasty, and chronic kidney disease was diagnosed with retroperitoneal paraganglioma when he presented with abdominal mass and elevated urine normetanephrine and 3-methoxytyramine. CECT abdomen revealed a large lesion arising from the inferior vena cava (IVC) measuring 9.3 × 9.0 × 13 cm. Biopsy was consistent with moderately differentiated paraganglioma with functional scan evidence of MIBG-avid disease. Multidisciplinary team discussion deemed the tumour inoperable due to size and high vascular risk. Chemotherapy with temozolomide was not suitable due to comorbidities. The patient was given one dose of 200 mCi of I-131 MIBG. He was stable throughout the admission. However, on day 21 post-therapy, he presented with chest pain and palpitations with a heart rate of 225 beats per minute. ECG showed monomorphic ventricular tachycardia which reverted to sinus rhythm with intravenous amiodarone infusion. A subsequent cardiac MRI showed normal left ventricular function and ejection fraction, with no features of myocardial infarction or infiltration. CONCLUSION This case highlights a rare but significant complication of I-131 MIBG therapy in the form of ventricular arrhythmia, likely triggered by catecholamine release from tumour lysis. Close cardiac monitoring is essential, especially in patients with pre-existing cardiovascular comorbidities undergoing MIBG treatment.